The Temperature of the Dimethylhydrazine Drops Moving in the Atmosphere after Depressurization of the Fuel Tank Rockets; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Bulba E. E. Elena Evgenievna (2016, 2016)
Title screen